From Queens to Slaves Pope Gregory's Special Concern for Women. - Martyn, John R. C. (Newcastle upon Tyne : Cambridge Scholars Pub., 2011)
The book is based on the author's very careful study of all the women who were involved with the normally extremely busy and painfully sick Pope Gregory the Great, many of them staying with him in Rome while he sorted out their mainly legal cases, and one of them, Theoctista, the learned sister of the Emperor Maurice, receiving the longest letter that he ever wrote to any individual. The consular son of the great Boethius, Flavius, was the father of Lady Rusticiana, who received several lette ...
Table of contents; preface; historical background; chapter one; chapter two; chapter three; chapter four; chapter five; chapter six; chapter seven; chapter eight; chapter nine; bibliography; index of names.
Description based on print version record.
Keywords: Gregory -- I, -- Pope, -- approximately 540-604 -- Relations with women -- Sources; Women in the Catholic Church -- History -- To 1500.; Popes -- Correspondence; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books